VISI KEPEMIMPINAN DAN STRATEGI PEMIMPIN DALAM TEORI NAHWU - Damanhuri; Suroso (Ta'dibi : Jurnal Manajemen Pendidikan Islam, 2023)
This article describes the relationship between leadership vision and leader strategy based on Nahwu theory, one of the 12 sciences of Arabic. Nahwu theory provides a deep understanding of the structure of the Arabic language, enabling Arabic speakers to convey messages correctly and providing proper understanding of the Quran and Hadith. Sayyidina Ali bin Abi Talib, an Islamic figure, ordered the compilation of Arabic grammar rules (the science of Nahwu) in response to errors in reading the Quran among Muslims. Nahwu, as the science of grammatical rules, focuses on isim and fiil. This article discusses the concepts of isim and fiil, where isim refers to the name of a thing or idea, while fiil describes an action or activity involving a specific actor and time. In addition, the article discusses the concepts of mu'rob and mabni, related to the final state of the kalimah, and the discussion of nakiroh and makrifah which only apply to the isim kalimah. Leaders who understand Nahwu can apply effective leadership strategies, such as proper word selection, formation of effective sentence structures, adjustment to the context of communication, language consistency, and application of grammar rules. The success of the leader in creating a clean, structured and effective leadership vision will be reflected in his ability to convey messages clearly and in accordance with the desired norms and values.